Recent recommendations and guidelines in selected diseases of the alimentary tract - Paradowski, Leszek; Błoński, Wojciech (Przewodnik Lekarza/Guide for GPs, 2007)
This manuscript presents the most recent guidelines and recommendations in diagnosing and treating selected diseases of the alimentary tract such as gastroesophageal reflux disease, eosinophilic oesophagitis and Barrett’s oesophagus. In addition, we also present guidelines concerning colon cancer screening in people with average and high risk of developing colon cancer as well as in patients who underwent colonic resection due to colon cancer.